A Translation Analysis On Adjective In Stephenie Meyers Novel Breaking Dawn Into Awal Yang Baru By Monica Dwi Chresyani - Larasati, Sarita, Dwi Haryanti, Dra. M. Hum., Dr, Mauly Halwat Hikmat, Ph. D (2015)
The research paper aims at describing the translation analysis of adjectives found in novel Breaking Dawn by Stephenie Meyer into Awal Yang Baru by Monica Dwi C. The study aims at analyzing the type of translation shift of adjective, classifing the translation shifts of adjective found in novel Breaking Dawn by Stephenie Meyer into Awal Yang Baru by Monica Dwi C and describing the translation equivalence of the translation result. The type of this research is descriptive qualitative research. In collecting data, the writer uses documentation method. The data are analyzed using translation analysis theory according to Catford's (1965) theory. In the process of collecting data, the reseacher does some steps, namely: reading the novel and collecting the adjectives on the novel, noting the novel, analyzing the adjectives, coding the data of adjective. Theory of translation by Catford (1965) is used to analyze collected data. The result of the research shows that the reseacher found 221data of adjective that uses translation shift in novel Breaking Dawn by Stephenie Meyer into Awal Yang Baru by Monica Dwi C. The writer divides translation shift into two types of shift. There are category shift and level shift. It consists of 101 data or 45,70% of adjective belong to category/class shifts and 110 data or 49,77% of adjective belong to level shifts. From 221 data of adjective, the writer finds that all of the data of adjectives are equivalent translation and the writer does not find any data of adjective included in not equivalent translation. It means that the data is 100% equivalent. The result of this study is that the translator makes an equivalent translation.